Preliminary study on bagasse fiber with Polystyrene as polymer composites - Liyana Jamaludin (Universiti Malaysia Perlis, 2009)
The interest in long term sustainability of material resources has make advancements in bio-composites or else name as polymer composite materials which made from natural fibers and resins. Natural fibers reinforced with polymer composites have gained more interest because of their biodegradable, light weight, less expensive sources, easy processing, high specific modulus and also environmentally friendly appeal. The bagasse-fiber-based composite has a potential as the core material replacing high density and expensive wood-based fiberboard. This paper presents an overview study on how the bio-composites which is bagasse fibers combined with resins as an alternative of bagasse-fiber-based composites. Biodegradable composites reinforced with bagasse fibers after being modified or treated by alkali treatment were prepared and the mechanical properties were investigated. The bio-composites samples were processed by hot press machine. The temperature of hot press is between 170 ºC to 190 ºC. All bagasse composite were made with aspect composition between bagasse fibers and polystyrene thermoplastics resins. The composition between fiber and resin that has been used is 80:20, 70:30 and 60:40. The type of filler that was used is short fiber and combination of both short and granules fibers. The polystyrene was added as a modification from natural fibers to determine the effect on physical and mechanical properties of the bagasse composite. Conversely, the addition of polystyrene enhanced some physical properties. The value of compressive strength, bending strength and bending modulus increased in the resin content level and composite density. Static bending and water absorption also increased as the fiber composition is increased.